The Effect of Project-Based Learning on Students' Speaking and Interpersonal Communication Skills - Muhammad Rozani; Uky Eji Anggara; Wilda Afriani (Raja Zulkarnain Education Foundation, 2025)
This study aims to determine the influence and effectiveness of project-based learning on students’ speaking and interpersonal communication skills in Indonesian language subjects. The method used in this study is quantitative descriptive with a quasi-experimental design. This study involved two main classes, namely the experimental class and the control class. The research design used pre-tests and post-tests. Data analysis was conducted using a quantitative descriptive approach, using paired sample t-tests and independent sample t-tests. The results of this study indicate that project-based learning has a significant effect on students’ speaking and interpersonal communication skills. This can be seen from the significance value (two tails) of 0.001, which is smaller than 0.05. This means that there is a significant difference in students’ speaking skills after implementing the project-based learning model. Similarly, interpersonal communication skills also experienced a significant increase, namely a significant difference in the application of project-based learning on students’ interpersonal communication skills. This is evidenced by a significance value (two tails) of 0.001, which is smaller than 0.05. The implications of these research results reinforce that project-based learning can improve speaking skills and build communication skills through structured social practices.